Switching to the Mac the missing manual - Pogue, David (O'Reilly Media, 2015)
What makes Windows refugees decide to get a Mac? Enthusiastic friends? The Apple Stores? Great-looking laptops? A "halo effect" from the popularity of iPhones and iPads? The absence of viruses and spyware? The freedom to run Windows on a Mac? In any case, there?s never been a better time to switch to OS X?and there?s never been a better, more authoritative book to help you do it. Learn Yosemite. Apple?s latest operating system is faster, smarter, and more in tune with iPads and iPhones. If Yosemite has it, this book covers it. Get the expert view. Learn from Missing Manuals creator David Pogue?author of OS X Yosemite.